Oral exposure to dibutyl phthalate exacerbates chronic lymphocytic thyroiditis through oxidative stress in female Wistar rats - Yang Wu (Nature Portfolio, 2017)
Abstract Chronic lymphocytic thyroiditis (CLT) is a common autoimmune disorder. The possible pathogenic role and mechanism of dibutyl phthalate (DBP) in CLT is still controversial. Experiments were conducted after 35-days of oral exposure to the three concentrations of DBP or saline, and three immunizations with thyroglobulin (TG). Healthy female Wistar rats were randomly divided into ten exposure groups (n = 8 each): (A) saline control, (B) 0.5 mg/kg/d DBP, (C) 5 mg/kg/d DBP, (D) 50 mg/kg/d DBP, (E) TG-immunized group, (F) TG- combined with 0.5 mg/kg/d DBP, (G) TG- combined with 5 mg/kg/d DBP, (H) TG- combined with 50 mg/kg/d DBP, (I) TG- combined with 50 mg/kg/d DBP plus 100 mg/kg/d vitamin C; (J) 100 mg/kg/d vitamin C. We showed that oral exposure DBP can aggravate CLT in rats. This deterioration was concomitant with increased thyroid auto antibodies, Th1/Th2 imbalance and Th17 immune response, activated pro-inflammatory and apoptosis pathways, and increased thyroid dysfunction in rats. Our results also suggested that DBP could promote oxidative damage. The study also found that vitamin C reduced the levels of oxidative stress and alleviated CLT. In short, the study showed that DBP exacerbated CLT through oxidative stress.